2017
DOI: 10.1242/dev.144337
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in neural development: from master regulators to fine-tuners

Abstract: The proper formation and function of neuronal networks is required for cognition and behavior. Indeed, pathophysiological states that disrupt neuronal networks can lead to neurodevelopmental disorders such as autism, schizophrenia or intellectual disability. It is wellestablished that transcriptional programs play major roles in neural circuit development. However, in recent years, post-transcriptional control of gene expression has emerged as an additional, and probably equally important, regulatory layer. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
185
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(188 citation statements)
references
References 172 publications
(174 reference statements)
3
185
0
Order By: Relevance
“…Increasing miRNAs are considered to be clinical biomarkers for atherosclerosis (Feinberg & Moore, ). Many recent studies have indicated that miRNAs can control a lot of fundamental biological processes (Rajman & Schratt, ; Zhang et al, ). For example, miR‐100 can inhibit chronic vascular inflammation by stimulating endothelial autophagy (Pankratz et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing miRNAs are considered to be clinical biomarkers for atherosclerosis (Feinberg & Moore, ). Many recent studies have indicated that miRNAs can control a lot of fundamental biological processes (Rajman & Schratt, ; Zhang et al, ). For example, miR‐100 can inhibit chronic vascular inflammation by stimulating endothelial autophagy (Pankratz et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, there are numerous reports that revealed the roles of various miRNA in neuronal development and differentiation. The important functional roles of miRNA in neurogenesis, neuroprotection, survival, and pathogenesis of neuropsycho‐disorders have been also extensively studied and reviewed . In addition, alterations of miRNA are reported to be associated with many neuropsychiatric diseases.…”
Section: Mirna Biogenesis and Functions In The Cnsmentioning
confidence: 99%
“…In support, Konopka et al found the enhanced learning and memory in adult mice with tamoxifen‐induced deletion of Dicer1 gene. However, when using knockout mouse models, some consideration should be taken into account as pointed out by Rajman . Indeed, Dicer1 has been proved to be essential for cell survival and embryonic development.…”
Section: Dysregulation Of Mirnas In Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation
“…Sustained high concentrations of ox-LDL can stimulate vascular endothelial cells, upregulate the expression of the autophagy-related proteins beclin 1 and lipidated microtubule-associated protein light chain 3, increase intracellular Ca 2þ concentration, induce endoplasmic reticulum stress (ERS), and induce the expression of the pro-apoptosis proteins JNK (mitogen-activated protein kinase 8) and CHOP (DNA damage inducible transcript 3), leading to vascular endothelial cell apoptosis (Muller et al, 2011). Accumulating studies have demonstrated that miRNAs are involved in various physiological and biochemical reactions in mammals, such as stem cell pluripotency maintenance and directional differentiation regulation, organogenesis, developmental regulation, tumorigenesis and tumor progression, and the pathogenesis of ageing (Cheng et al, 2012;Liu et al, 2013;Moran et al, 2017;Rajman and Schratt, 2017). Therefore, ox-LDL plays an important role in atherosclerosis progression.…”
Section: Introductionmentioning
confidence: 99%